Disobedience of Constitutional Court Decision as a Reason for Impeachment of President and Vice President - Pahlawan MP, H. Muhamad Rezky; Adhistianto, Mohamad Fandrian; Nunna, Bhanu Prakash (Al-Risalah, 2024)
This article discusses disobedience of the Constitutional Court Decision Number 91/PUU-XVIII/2020 which was carried out by the Government by issuing Minister of Home Affairs Instruction Number 68 of 2021 Concerning Follow-Up of the Constitutional Court Decision Number 91/PUU-XVIII/2020 Regarding the Formal Review of Law Number 11 of 2020 concerning Job Creation which in essence states that it remains guided and implement Law Number 11 of 2020 concerning Job Creation and its Implementing Regulations. This instruction from the Minister of Home Affairs has violated one of the rulings stating that the legally binding force of Law Number 11 of 2020 concerning Job Creation must be temporarily suspended for 2 (two) years or until the process of its formation has been repaired. This study uses a statutory approach and a conceptual approach and is also evaluated descriptively and qualitatively. The conclusion of this paper is that disobedience to the constitution by the Government will have a juridical impact on not realizing legal certainty, impacting people's distrust of the Constitutional Court, as well as a bad example given by the President in terms of constitutional awareness, so that it is appropriate for the DPR RI to file an impeachment process against the president